Remue-méninges dans les sciences du genre, Entretien avec Rebecca Jordan-Young - Mozziconacci, Vanina (Emulations - Revue de sciences sociales, 2018)
Number: 15
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inégalités; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Racisme et santé mentale – Jade Almeida - Almeida, Jade (2018)
Cette émission n°72 est consacrée à la santé mentale à travers différents sujets, différentes sources, différents territoires ; Trinidad, Canada, Sénégal, France… On y parle exil, enfermement, complicité, famille, isolement, etc. Bonne écoute !
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; discours dominant; fem3300; premier cycle; périodes historiques; racisme; ressource en ligne; santé; santé mentale; systèmes d'oppressions; thématiques

Gender and the Building Up of Many ‘Peaces’: A Decolonial Perspective from Colombia dans Gender, conflict, peace, and UNSC resolution 1325 - Anctil Avoine, Priscyll; Tillman, Rachel; Mejía Jerez, Yuly Andrea (Gender, conflict, peace, and UNSC resolution 1325, 2018)
As we write this chapter about reinterpreting women’s roles in peacebuilding, Colombia is at a turning point. On November 24, 2016, the Revolutionary Armed Forces of Colombia—People’s Army (FARC-EP) and the national government signed a historical agreement that ended the 60-year-long armed conflict. How this peace and the social reconciliation that it requires will be implemented remain to be seen. At the peace negotiations roundtable, throughout the early years of the conversations, women were underrepresented, and even now gender inequality within public participation is far from being resolved. Although women have been acting equally with their male counterparts as rotating negotiators in these peace negotiations, the High Commissioner for Peace (Alto Comisionado para la Paz) affirms that only 25 percent of the plenipotentiary negotiators are women, and that while the Gender Subcommittee is an interesting accomplishment, it is still insufficient. Additionally, Colombia is facing the challenge of FARC-EP’s reintegration to civil society: between 33 percent and 40 percent of their troops are women and most of the DDR processes do not show a serious focus on gender in their programs.
Section: ix, 278 pages
Keywords: 2000 à aujourd'hui; 2010-2019; amérique latine; amériques; approches et analyses; colombie; corps; cours; discipline; féminisme décolonial; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; système colonial; systèmes d'oppressions; thématiques; violences

Territoires de libération : perspectives féministes musulmanes - Benhadjoudja, Leïla (Tumultes, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discipline; discours dominant; fem3400; féminisme islamique; féminisme musulman; histoire et politique; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques

“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Le racisme est un problème de blancs - Eddo-Lodge, Reni; Mazoyer, Renaud (Éditions Autrement, 2018)
« Quand des Blancs feuillettent un magazine, surfent sur Internet ou zappent à la télévision, il ne leur semble jamais étrange de voir des gens qui leur ressemblent en position d'autorité. Les affirmations positives de la blanchité sont tellement répandues que le Blanc moyen ne les remarque même pas. Etre blanc, c'est être humain ; être blanc, c'est universel. Je ne le sais que trop, car je ne suis pas blanche." Après l'élection de Barack Obama, certains ont proclamé l'avènement d'une société post-raciale. Avec une liberté de ton décapante, Reni Eddo-Lodge montre ici combien nous en sommes loin. Elle analyse les méfaits d'un racisme structurel persistant d'autant plus sournois qu'il avance masqué. Car le racisme va bien au-delà de la discrimination ou de l'injure personnelle. Il imprègne le récit historique, l'imaginaire collectif, les institutions et les entreprises. Pourquoi les Blancs pensent-ils ne pas avoir d'identité raciale? Pourquoi la simple idée d'un James Bond noir fait-elle scandale? Comment une fillette noire en vient-elle à se persuader qu'en grandissant, elle deviendra blanche? Le racisme n'est pas une question de valeur morale, mais d'exercice du pouvoir. Entretenir la légende d'une égalité universelle n'aide en rien. Au contraire. Car, pour déconstruire le racisme, il faut commencer par reconnaître l'étendue du privilège blanc. »– 4ème de couverture.
Section: 290 pages ; 21 cm
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afro-féminisme; approches et analyses; com5170; communication; cours; discipline; europe; féminisme afropéen; histoire et politique; journalisme; premier cycle; privilèges; périodes historiques; racisme; racisme systémique; représentation des femmes* racisées; royaume-uni; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Le podcast continue en 2024 sur une nouvelle plateforme https://pseudo-radio.com/podcasts/kiffe-ta-race/
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences

“Disability Justice” is simply another term for love - Mingus, Mia (Leaving Evidence, 2018)
This was the opening keynote speech at the 2018 Disability Intersectionality Summit, in Cambridge, Massachusetts on Oct 13, 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capacitisme; corps; cours; discours dominant; fem3300; genre; identités LGBTQIA2+; militance; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis